Characterization of Ti-25.5Al-13.5Nb-2.8Mo-1.8Fe Alloy Hot Deformation Behavior Through Processing Map - Cheng, Jun; Du, Zhaoxin; Zhang, Xiaoyong; Zhang, Wen; Gai, Jinyang; Li, Jinshan (Frontiers in Materials, 2020)
The isothermal compression tests of Ti-25.5Al-13.5Nb-2.8Mo-1.8Fe (at.%) alloys were executed under the deformation temperature ranges of 950-1100 C with the strain rate ranges of 0.001-1 s-1, for total height reduction of 0.5. The isothermal compression deformation behavior was investigated based on flow stress curves, dynamic model analysis. The processing map of Ti-25.5Al-13.5Nb-2.8Mo-1.8Fe alloy was obtained for the optimum hot process parameters. The calculated value of Q (activation energy) was 634.5 kJ/mol. The constitutive model of the alloy was constructed. Based on DMM and the Prasad flow instability criteria, the hot processing map was established with strain of 0.7. The deformation mechanisms were interpreted by microstructural observation within both stable and instability zones. Processing map showed a stable region under the deformation temperature ranges of 950-1100 C with the strain rate ranges of 0.001-1 s-1. One certain maximum power dissipation efficiency value was approximately 43 % occurred at 950 C/0.001 s-1. Another peak power dissipation efficiency value was about 58 % at 1050 C/0.001 s-1. Both areas were the optimum processing regions. Furthermore, while the strain rate value exceeded 1 s-1, the alloy sustained deformation instability phenomenon, such as shearing band or flow localization.